A simple prognostic score based on troponin and presepsin for COVID-19 patients admitted to the emergency department: a single-center pilot study: Presepsin and Troponin in ED triage for COVID-19 patients. - Dell'Aquila, Paola; Raimondo, Pasquale; Orso, Daniele; De Luca, Paola; Pozzessere, Pietro; Parisi, Carmen Vita; Bove, Tiziana; Vetrugno, Luigi; Grasso, Salvatore; Procacci, Vito (Acta Biomedica Atenei Parmensis, 2021)
Background: The need to determine prognostic factors that can predict a particularly severe or, conversely, the benign course of COVID-19 is particularly perceived in the Emergency Department (ED), considering the scarcity of resources for a conspicuous mass of patients. The aim of our study was to identify some predictors for 30-day mortality among some clinical, laboratory, and ultrasound variables in a COVID-19 patients population.Methods: Prospective single-center pilot study conducted in an ED of a University Hospital. A consecutive sample of confirmed COVID-19 patients with acute respiratory failure was enrolled from March 8th to April 15th, 2020.Results: 143 patients were enrolled. Deceased patients (n = 65) were older (81 vs. 61 years, p